Productivity Analysis of Rice Farming System in Riam Kanan Irrigated Area Banjar, South Kalimantan - Mustaniroh, Siti Asmaul; Hartono, Slamet (Jurnal Teknologi Pertanian, 2000)
Irrigation of Riam Kanan is project financed by Japanese Government withpotential area 25,900 hectare, which covered sub area A,B,C,D and E. The purpose ofthe project was to fulfill the need of all plants according to planting pattern that wasschedule, technically through system and drainage.Â The research has purposed to recognize Riam Kanan irrigation establishment effecton frequency of plantation, productivity and income of rice farming system.Â To get data in this research use methods survey and observation, respondent orfarmer objects by random data shortinity. Research result showed that Rian Kananirrigation project can increase frequency of plantation, productivity and income of ricefarming system, although not optimally obtained. For all condition is enough to realizethat result of rice farming system irrigated area higher than unirrigated area.Key words: productivity analysis, Riam Kanan irrigation project